Cluster headache: trial of a combined histamine H1 and H2 antagonist treatment. Issue 7 (July 1979) - Russell, D
Abstract : Fifteen patients with symptomatic cluster headache participated in a double-blind crossover trial of a combined histamine H1 and H2 antagonist treatment. The trial lasted six weeks. There was no significant improvement on active treatment as regards mean number of headache attacks per week, intensity, or duration of attacks. These results suggest that histamine does not play a significant role in the pathogenesis of cluster headache.